2012
DOI: 10.1002/pri.1543
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term and Long‐term Effects of Electrical Stimulation on Skin Properties

Abstract: Electrical stimulation caused temporary increase in TEWL with no effects on other skin properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Nevertheless, it is still unknown why vasodilatation under the anode is often different than under the cathode. Possible mechanisms include pH changes in different directions depending on stimulation polarity (Almalty et al, 2013; Ezquerro et al, 2017; Minhas et al, 2010). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…Nevertheless, it is still unknown why vasodilatation under the anode is often different than under the cathode. Possible mechanisms include pH changes in different directions depending on stimulation polarity (Almalty et al, 2013; Ezquerro et al, 2017; Minhas et al, 2010). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…Users of all types of electrical stimulators must be informed and warned about their adverse effects. Studies have shown that all types and configurations of electrical waves can increase the skin's permeability to topical medications and other chemical products that can be applied to the skin during or after ES sessions 16,18 . Therefore, the manufacturers of these devices must include a warning in the user manual regarding the potential for skin irritation when using chemical products during or immediately after using ES.…”
Section: Discussionmentioning
confidence: 99%
“…found that the transient change in permeability is not restricted to the regions beneath the electrodes but also includes the space between them. 16 And as a consequence of this increased permeability, both drugs and irritant chemicals can more easily permeate the epidermis.…”
Section: Baselinementioning
confidence: 99%
“…This was also evident in the sensitivity analysis of the tissue conductivities, which revealed the potential to change by up to approximately 1.5 V when increasing the conductivity of the different skin layers. The moisture content of the stratum corneum has a high impact on impedance values and may change over the time course of stimulation as the transepidermal water loss increases when applying electrical stimulation [37]. Apart from hydrating the stratum corneum, the increase in transepidermal water loss may introduce more moisture to the electrode-skin interface.…”
Section: Study Limitationsmentioning
confidence: 99%